TRADISI PERNIKAHAN ADAT KARO DI DESA KUTA GALUH KECAMATAN TIGANDERKET MENURUT HUKUM ISLAM - Idola Berkah Hidayat, Abu Bakar, Jamaluddin (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
Customs and culture are something that must be preserved as a legacy from our ancestors since ancient times. However, if the tradition or culture is contrary to the teachings of our beliefs, namely Islamic law, then the custom must be set aside and take a path that is in accordance with the guidance in Islam. Basically a marriage is said to be valid in Islamic teachings if the marriage has fulfilled the pillars and conditions that have been determined by Islamic law in accordance with the provisions of Islamic law. However, in addition to obtaining legality in marriage, a person who carries out a marriage must maintain chastity in undergoing the marriage process. The tradition of Nangkih, rebu and the prohibition of marrying women of the same clan are examples of cultural heritage in Karo customs that must be studied in order to determine the law whether the above traditions are in line with Islamic law or vice versa, namely contrary to Islamic law.